Strongly asymmetric interactions and control regimes in the Barents Sea: a topological food web analysis - Jordán, Ferenc; Capelli, Greta; Primicerio, Raul; Bodini, Antonio (Frontiers in Marine Science, 2024)
Introduction Increasing temperature of the global ocean alters the spatial behavior of a number of species. From the northern Atlantic Ocean, species may shift their area towards the poles. This results in the atlantification of the Barents Sea, raising questions about possible changes in species composition, community structure and community control. Methods We address the question whether possible changes in community control can be detected and quantified based on simple network analytical measures applied to the food web. Based on unweighted (binary) and undirected (symmetric) data, we quantify the strength of direct and indirect interactions in the network, represent the most asymmetric effects in the asymmetry graph composed of directed and weighted links and study the overlap among trophic niches of organisms. Results and discussion We support earlier findings suggesting that the ecosystem can possibly be characterized by wasp-waist control. This would mean that focusing management efforts on intermediate trophic levels is of high importance, providing indirect benefit for organisms also at lower and higher trophic levels.